Development of a new single unit dosage form of propranolol HCl extended release non-effervescent floating matrix tablets: In vitro and in vivo evaluation - Rajendra Kumar Jadi & , Ramesh Bomma, Velmurugan Sellappan (Journal of Applied Pharmaceutical Science, 2016)
The objective of the present investigation was to develop extended release non-effervescent floating matrix tablets of Propranolol Hydrochloride (PPH) to extend the gastric residence time (GRT) and prolong the drug release after oral administration. Different viscosity grades of Hydroxypropyl methylcellulose (HPMC) polymers such as HPMC K4M, HPMC K15M and HPMC K100M were used as drug release retardants. Glyceryl behinate (Compritol 888 ATO) and Glyceryl monosterate (Precirol ATO 5) were used as low density lipids in order to get the desired buoyancy over a prolonged period of time. The drug excipients compatibility study was carried out by using Differential Scanning Calorimetry (DSC). All the formulations were prepared by direct compression technique. The prepared tablets were evaluated for their physical characters, in vitro drug release and in vitro buoyancy. The release and floating property depends on the polymer type, polymer proportion, lipid type and lipid proportions. The drug release profiles of all the formulations were subjected to Zero order, First order, Higuchi and Peppas kinetic models, and the optimized formulation (F7) followed the Peppas model (R2= 0.987) with non-Fickian diffusion mechanism(n>0.5). The optimized formulation was subjected for in vivo radiographic studies in healthy human volunteers (n=3). These studies revealed a mean gastric residence time of 5±1.73 h (n=3).
Keywords: Propranolol HCl,Compritol 888 ATO,Precirol ATO 5,Non-effervescent,Floating drug delivery system and Gastric residence time.